Eksistensi Pemberian Bantuan Hukum Terhadap Anggota Tentara Nasional Indonesia-Angkatan Darat Yang Melakukan Tindak Pidana - Sahlepi, Muhammad Arif (Universitas Islam Sumatera Utara, 2024)
This article aims to analyze the current social life that should be equipped with military forces or often known as the Indonesian National Army as an apparatus that defends the sovereignty of the state and protects and protects the community from military and armed threats. In the regulation of legal aid to soldiers who commit criminal acts in accordance with the rules of legal aid according to the military justice law, criminal sanctions given to soldiers who commit criminal acts such as getting military disciplinary sanctions, imprisonment, administrative and scorcing or PTDH (Dismissal Not Honorably). the regulation of legal aid to Indonesian Army Soldiers who commit criminal acts, is regulated in the regulation of legal aid according to KUHAP, according to the Military Justice Law, Law R.I. Number 34 of 2004 concerning the Indonesian National Army, Rules of the TNI Commander and its derivatives and according to Law R.I. Number 16 of 2011 concerning Legal Aid. Keywords: Provision of Legal Aid; Indonesian National Army